Serum amyloid A is independently associated with metabolic risk factors but not with early atherosclerosis: the Cardiovascular Risk in Young Finns Study - Jylhävä, J.; Haarala, A.; Eklund, C.; Pertovaara, M.; Kähönen, M.; Hutri‐Kähönen, N.; Levula, M.; Lehtimäki, T.; Huupponen, R.; Jula, A.; Juonala, M.; Viikari, J.; et al. (Journal of internal medicine, 2009)
. Background.  Serum amyloid A (SAA) is a sensitive marker of inflammation and its elevation has been implicated in obesity and in cardiovascular disease, yet data on its regulation in young adults or on its role in early atherosclerosis is scarce. We investigated which factors explain the variation in SAA and analysed whether SAA could be associated with preclinical atherosclerosis. Methods.  Serum amyloid A levels were measured in participants of the Cardiovascular Risk in Young Finns Study (n = 2280, n = 1254 women, n = 1026 men). Correlates and determinants of SAA were analysed and the effect of SAA on subclinical atherosclerosis, measured as intima‐media thickness (IMT) and carotid artery compliance, was evaluated with risk‐factor adjusted models. Results.  Serum amyloid A correlated directly and independently of BMI with C‐reactive protein (CRP), waist circumference and leptin in both sexes, with total cholesterol, LDL cholesterol and ApolipoproteinA1 (ApoA1) in women and with triglycerides, insulin levels and insulin resistance in men. Use of combined oral contraceptives and intrauterine device was also associated with SAA levels. Determinants for SAA included CRP, leptin and ApoA1 in women, and CRP, leptin and HDL cholesterol in men. SAA levels correlated with carotid compliance in both sexes and with IMT in men, yet SAA had no independent effect on IMT or carotid compliance in multivariable analysis. Conclusions.  Serum amyloid A was associated with several metabolic risk factors but was not an independent predictor of IMT or carotid artery compliance. Further longitudinal studies will show whether SAA holds a prognostic value as a risk marker, analogously to CRP.